The Influence of Problem Based Learning Model on Social Attitudes and Collaboration Skills of Fifth Grade Students in Social Sciences Subject - Ni Nyoman Kurnia Wati; Lasmawan, I Wayan; Kertih, I Wayan; Sukmayasa, I Made Hendra (Jurnal Pendidikan dan Pengajaran, 2023)
Learning social science is still centered on the teacher, therefore it is necessary to have an innovative learning model that can foster collaboration skills and social attitudes of students. The purpose of this study was to analyze the effect of the problem based learning model on social attitudes and collaboration skills. This research is included in the quasi-experimental research. The number of samples used in this study were 44 students, consisting of 21 students as the experimental class. The independent variable was the problem-based learning model. While the dependent variable is social attitudes and students' collaboration skills. The data collection method in this study used the questionnaire method and the observation method. Hypothesis testing using Manova analysis. The results of the study show that 1) there is a significant influence of the problem-based learning model on social attitudes. 2) There is a significant effect of the problem-based learning model on collaboration skills 3) Simultaneously, there is a significant effect of the problem-based learning model on social attitudes and collaboration skills of social studies content.